Bone mineral density in elite adolescent female figure skaters. - Prelack, Kathy.; Dwyer, Johanna.; Ziegler, Paula.; Kehayias, Joseph J. (2016)
Abstract: Elite adolescent figure skaters must accommodate both the physical demands of competitive training and the accelerated rate of bone growth that is associated with adolescence, in this sport that emphasizes leanness. Although, these athletes apparently have sufficient osteogenic stimuli to mitigate the effects of possible low energy availability on bone health, the extent or magnitude of bone accrual also varies with training effects, which differ among skater disciplines.; Keywords: Dual Energy Photon Absorptiometry, Bone Mineral Density, Total Body, Leg, Spine, Pelvis, Grams Per Centimeter Squared, Body Mass Index, Standard Deviation.; Springer Open.